2021
DOI: 10.3389/fpsyg.2021.633228
|View full text |Cite
|
Sign up to set email alerts
|

Superior Performance in Skilled Golfers Characterized by Dynamic Neuromotor Processes Related to Attentional Focus

Abstract: The meshed control theory assumes that cognitive control and automatic processes work together in the natural attention of experts for superior performance. However, the methods adopted by previous studies limit their capacity to provide in-depth information on the neuromotor processes. This experiment tested the theory with an alternative approach. Twelve skilled golfers were recruited to perform a putting task under three conditions: (1) normal condition, with no focus instruction (NC), (2) external focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…6 WANG, CHENG, CHEN, LIN, HUANG, SCHACK, AND HUNG (Lo et al, 2019). As the left temporal region (i.e., T7) is associated with verbal-analytical processes (Haufler et al, 2000), these studies suggest that reduced cortico-cortical communication between the verbal-analytical (i.e., T7) and motor planning regions (i.e., Fz) indicates a decrease in the explicit monitoring of movement during motor preparation (Cheng et al, 2017;Deeny et al, 2003Deeny et al, , 2009Gallicchio et al, 2016Gallicchio et al, , 2017Hatfield, 2018;Lo et al, 2019;Wang et al, 2020Wang et al, , 2021. Lower α coherence at Fz-T7 may therefore be associated with the inhibition of non-essential cognitive processes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…6 WANG, CHENG, CHEN, LIN, HUANG, SCHACK, AND HUNG (Lo et al, 2019). As the left temporal region (i.e., T7) is associated with verbal-analytical processes (Haufler et al, 2000), these studies suggest that reduced cortico-cortical communication between the verbal-analytical (i.e., T7) and motor planning regions (i.e., Fz) indicates a decrease in the explicit monitoring of movement during motor preparation (Cheng et al, 2017;Deeny et al, 2003Deeny et al, , 2009Gallicchio et al, 2016Gallicchio et al, , 2017Hatfield, 2018;Lo et al, 2019;Wang et al, 2020Wang et al, , 2021. Lower α coherence at Fz-T7 may therefore be associated with the inhibition of non-essential cognitive processes.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are also concordant with other studies that demonstrate lower levels of cortico-cortical communication between T7 and Fz in highly skilled performers than in less skilled performers (Deeny et al, 2003(Deeny et al, , 2009; in the best performing than in the worst performing skilled pistol shooters (Cheng et al, 2017); and in non-stressful than in stressful conditions in terms of dart throwing performance (Lo et al, 2019). As the left temporal region (i.e., T7) is associated with verbal-analytical processes (Haufler et al, 2000), these studies suggest that reduced cortico-cortical communication between the verbal-analytical (i.e., T7) and motor planning regions (i.e., Fz) indicates a decrease in the explicit monitoring of movement during motor preparation (Cheng et al, 2017;Deeny et al, 2003Deeny et al, , 2009Gallicchio et al, 2016Gallicchio et al, , 2017Hatfield, 2018;Lo et al, 2019;Wang et al, 2020Wang et al, , 2021. Lower α coherence at Fz-T7 may therefore be associated with the inhibition of non-essential cognitive processes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the reason for the null result might be attributed to the attention conditions we compared. Previous studies found a stronger T7-Fz connection for internal focus compared to external focus (Ellmers et al, 2016;Wang et al, 2021). It is possible that an external focus condition is necessary to observe weaker T7-Fz connectivity.…”
Section: Figurementioning
confidence: 82%
“…Such manipulation checks ensure that participants read the instructions, but they do not ensure that they use the assigned attentional focus. To examine the latter, it is suggested to implement a dual-task paradigm when applicable and/or an electroencephalogram (EEG; see Wang et al, 2021 for an example of the relationships between EEG and attentional focus).…”
Section: Discussionmentioning
confidence: 99%